A CRISPR/Cas9 mediated point mutation in the alpha 6 subunit of the nicotinic acetylcholine receptor confers resistance to spinosad in Drosophila melanogaster. - Zimmer, C.T.; Garrood, W.T.; Puinean, A.M.; Eckel-Zimmer, M.; Williamson, M.S.; Davies, T.G.; Bass, C. (Insect Biochemistry and Molecular Biology, 2016)
Spinosad, a widely used and economically important insecticide, targets the nicotinic acetylcholine receptor (nAChRs) of the insect nervous system. Several studies have associated loss of function mutations in the insect nAChR ?6 subunit with resistance to spinosad, and in the process identified this particular subunit as the specific target site. More recently a single non-synonymous point mutation, that does not result in loss of function, was identified in spinosad resistant strains of three insect species that results in an amino acid substitution (G275E) of the nAChR ?6 subunit. The causal role of this mutation has been called into question as, to date, functional evidence proving its involvement in resistance has been limited to the study of vertebrate receptors. Here we use the CRISPR/Cas9 gene editing platform to introduce the G275E mutation into the nAChR ?6 subunit of Drosophila melanogaster. Reverse transcriptase-PCR and sequencing confirmed the presence of the mutation in D?6 transcripts of mutant flies and verified that it does not disrupt the normal splicing of the two exons in close vicinity to the mutation site. A marked decrease in sensitivity to spinosad (66-fold) was observed in flies with the mutation compared to flies of the same genetic background minus the mutation, clearly demonstrating the functional role of this amino acid substitution in resistance to spinosad. Although the resistance levels observed are 4.7-fold lower than exhibited by a fly strain with a null mutation of D?6, they are nevertheless predicated to be sufficient to result in resistance to spinosad at recommended field rates. Reciprocal crossings with susceptible fly strains followed by spinosad bioassays revealed G275E is inherited as an incompletely recessive trait, thus resembling the mode of inheritance described for this mutation in the western flower thrips, Frankliniella occidentalis. This study both resolves a debate on the functional significance of a target-site mutation and provides an example of how recent advances in genome editing can be harnessed to study insecticide resistance.